The Influence of Patients’ Characteristics with Intravena Catheter in Phlebitis Incidence - Nella Mega Fadhilah Haritya Akbar; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2018)
Background: The phlebitis incidence was found as the fourth highest infection in hospitalized patients. Indonesia has contributed in phlebitis incidence as the fifth highest in the world wide after India, Iran, Malaysia, and Philippines. Purpose: This study was aimed to analyze the influence of patients’ characteristic with intravena catheter to phlebitis incidence. Methods: The study design was case control study with 45 respondents in case group (diagnosed with phlebitis) and control (undiagnosed with phlebitis) group in public hospital Haji Surabaya from January to April 2017. The independent variables in this study were age, sex, nutrioninal status, hypertension history, and diabetes mellitus history. Meanwhile, the dependent variable was phlebitis incidence. Data were analyzed with multiple logistic regression. Results: Phlebitis was influenced by patients’ characteristics namely age (p = 0,01; OR = 9,63; 95% CI =3,67 < OR < 25,25), sex (p = 0,01; OR = 4,84; 95% CI =1,85 < OR < 12,66), nutritional status (p = 0,01; OR = 4,01; 95% CI = 1,69 < OR < 9,66), hypertension history (p = 0,01; OR = 6,18; 95% CI = 2,47 < OR < 15,51), and diabetes mellitus history (p = 0.01; OR = 17.88; 95% CI = 6,05 < OR < 52,85). Conclusion: Patients’ characteristics had influence on phlebitis incidence such as age, sex, nutritional status, hypertension history, and diabetes mellitus history.